Study of Strength Characteristics of Products Produced by 3D-Printing from PLA - V. A. Ermakova; E. V. Gasperovich; A. I. Ermakov; V. V. Litvyak (Наука и техника)
In modern mechanical engineering, along with reducing the metal consumption of structures, the main task is  to increase the reliability and durability of parts, assemblies of mechanisms. This problem never loses its relevance due to the ever-increasing requirements for manufacture of products, with the need to save scarce expensive metals and alloys and,  as a result, replace them with economically more profitable options. One of the most promising, from the point of view of ecology, ways to replace metals, is to use in the construction of plastic assemblies, in particular polylactic acid (PLA). PLA is a biodegradable thermoplastic used in 3D-printing. The paper presents results of an experimental study on the rupture of samples obtained by 3D-printing from PLA under various technological operating modes of 3D-printer. The following parameters have  been chosen as variable parameters: the form of filling samples (triangle, hexagon (honeycomb), line, edge), nozzle temperature (190–205 °С), sample filling factor (from 10 up to 40 %). Tensile testing of the samples have been carried out on a hydraulic tensile machine with a measuring software package in the Kason WDW-5 set. When performing tests, the conditional yield strength was considered the main out put indicator. The analysis of experimental data has shown a significant effect of the investigated technological parameters on the conventional yield point, which varied from 16.5 to  22.42 MPa. The most rational forms and sample filling factor, as well as the temperature of nozzle when printing with PLA, have been determined.